Initial and Final Status of the Patients with Niemann Pick A and B: Ege University Experience - Ebru Canda; Havva Yazıcı; Esra Er; Sema Kalkan Uçar; Hüseyin Onay; Eser Sözmen; Ferda Özkınay; Mahmut Çoker (Galenos Yayinevi, 2018)
Aim:Niemann-Pick disease (NPD) is a lysosomal storage disease caused by an insufficient activity of acid sphingomyelinase (ASM) resulting in the accumulation of sphingomyelin. Type A is an infantile neurovisceral fatal form characterized by hepatosplenomegaly and rapidly progressive neurological deterioration, while the Type B non-neuronopathic disease presents visceral form and sufferers usually survive into adulthood.Materials and Methods:Here we present clinical and molecular findings for 19 patients with NPD A/B. Results:Nineteen patients with ASM deficiency were enrolled in our study. Nine of them were female and ten patients were male. The median age of the patients was 7.5 years (minimum-maximum: 1-57 years), the median age at diagnosis was 3 years (minimum-maximum: 6 months-56 years). The median length of the follow up period was 4.07±3.8 years (range: 1 month-14 years). Eighteen patients had hepatosplenomegaly, one patient had splenomegaly. Pulmonary involvement was detected in 10 patients. Six patients died during follow up.Conclusion:Patients with Niemann Pick A/B have a high mortality and morbidity rate. There is a need for a safe and effective therapy for patients with NPD A/B to reduce splenomegaly, to improve liver and respiratory function and to reduce the rate of mortality and morbidity.